SPOKEN ANALYSIS OF INTERRUPTION IN RESEARCH SEMINAR - Riski Zulkarnain (Jurnal Konseling Pendidikan Islam, 2023)
This paper focus to analyze interruptions among presenter, advisors, examiners, and audiences in research seminar forum. This research based on a study conducted in 2022 at Post Graduate Program State University of Makassar, South Sulawesi, Indonesia. To collect data, the researcher recorded the research seminar were obtained, transcribed, and analyzed by using discourse analysis approach. Interruption analysis. The results of this research are stated as follows, four types of interruption occurs through research seminar. They are simple interruption, overlap interruption, silent interruption and butting-in interruption. The highest frequency of the types of interruptions is simple interruption. Simple interruption appears 11extract, 1 times out of 26 total data extract. The lowest frequency is obtained by butting-in interruption with 2 data extract. This study is a kind of spoken discourse analysis which analyzes interruptions in research seminar interactions, it also includes identify the definition and described the types of those features which are different based on the context of interactions in research seminar.